Analysis of challenge request success according to contextual variables in elite badminton - Primo, L.; Gutiérrez-Suárez, A.; Gómez, M.-A. (6th World Congress of Racket Sport Science, 2018)
Badminton has evolved into a blink-and-miss event, with powerful smashes dominating rallies. Due to the fact that the speed of smashes have increased, there are controversial decisions when the shuttlecock hits the ground during the match. Therefore, the aim of the present study was to identify the importance of challenge request effectiveness in elite badminton according to contextual-related variables. The sample was composed of 56 shuttlecock challenge requested during 20 matches (quarter-final, semi-final or final matches) from the Olympic Games (Rio de Janeiro, 2016) and the Word Badminton Championship (Glasgow, 2017). The Crosstabs-Command and the Binomial logistic regression were applied in order to identify the interactive effects on challenge success of each contextual variable (gender, requester player, next point winner, score-line, game, game interval, games in favour, challenges left per game, match-outcome and player`s international experience). The main results identified that the success of a challenge is affected by the request with less efficiency when the player requests the hawk-eye (OR=0.65) and when the player that request the hawk-eye is the loser of the match (OR=0.21). The identified trends allow players to improve strategic plans that involve to select the most appropriate moment to request the calling Line Review.